Unveiling the pathways of Xuanbai Chengqi Decoction in obese asthma: from immune modulation to microbial restoration - Lu, Ke; Li, Chen; Zhang, Qingxiang; Li, HongXiang; Ding, Chen; Zhang, Lu; Cao, Feng (Frontiers in Nutrition, 2026)
BackgroundObesity asthma is a unique asthma phenotype, which has the characteristics of aggravation of clinical symptoms, change of immune response, and resistance to standard treatment. Obese asthma, as a clinical refractory asthma type, urgently needs effective and side-effect-free treatment. Xuanbai Chengqi Decoction (XBCQD) is a traditional Chinese medicine prescription widely used in the treatment of lung diseases, including asthma in China. However, the efficacy and mechanism of obese asthma remain to be explored.ObjectivesTo elucidate the therapeutic effect of XBCQD on obese asthma and reveal its mechanism.MethodsNetwork pharmacology was used to predict the potential therapeutic targets and pathways of XBCQD in the treatment of obese asthma. We established a mouse model of obese asthma by feeding a high-fat diet combined with intraperitoneal injection of ovalbumin (OVA) to induce sensitization, and then intervened with intragastric administration of high, medium, and low doses of XBCQD. During the modeling period, lung function and body weight of mice were used to evaluate the preparation of the obese asthma model. H&E staining, RT-qPCR, ELISA, Western blot, and flow cytometry were used to quantify Th cell subsets, 16S rRNA sequencing was used to determine microbial composition, and GC/MS was used to detect the content of short-chain fatty acids in intestinal contents to explore the mechanism of Xuanbai Chengqi Decoction on obese asthma.ResultsNetwork pharmacology showed that XBCQD may improve obese asthma by affecting core targets such as IL-6, TNF, and Caspase1, and through signaling pathways such as the IL-17 signaling pathway, AGE-RAGE signaling pathway, TNF signaling pathway, and Th17 cell differentiation. Experimental studies have found that XBCQD can alleviate the symptoms of obese asthma and lung inflammation, reduce serum IgE, reduce the expression of IL-6, IL-17, and IL-23 in serum, to reduce lung inflammation induced by obese asthma in mice; flow cytometry of spleen tissue showed that XBCQD reduced the proportion of Th17 cells and restored the proportion of Treg cells. Proteomics showed that XBCQD inhibited the expression of NLRP3, Caspase-1, and IL-1β by up-regulating the expression of GPR43, thereby inhibiting Th17-related protein RORγt and restoring Treg-related protein Foxp3, thereby regulating immune imbalance. At the same time, XBCQD restored the intestinal microbial species, and restored the beneficial bacteria such as Dubosiella, Akkermansia_muciniphila, Rikenella, which were reduced in obese asthmatic mice, and increased the content of acetic acid, propionic acid, and butyric acid in intestinal flora metabolites.ConclusionXBCQD regulates Th17/Treg immune imbalance in obese asthma by improving intestinal microecology and regulating SCFAs/GPR43/NLRP3 pathway. These findings provide new pharmacological evidence for its clinical application in obese asthma.